Musculoskeletal health: an ecological study assessing disease burden and research fundingResearch in context - Andrew T. Nguyen; Izzuddin M. Aris; Brian D. Snyder; Mitchel B. Harris; James D. Kang; Martha Murray; Edward K. Rodriguez; Ara Nazarian (The Lancet Regional Health. Americas, 2024)
Summary: Background: Exacerbated by an aging population, musculoskeletal diseases are a chronic and growing problem in the United States that impose significant health and economic burdens. The objective of this study was to analyze the correlation between the burden of diseases and the federal funds assigned to health-related research through the National Institutes of Health (NIH). Methods: An ecological study design was used to examine the relationship between NIH research funding and disease burden for 60 disease categories. We used the Global Burden of Disease (GBD) Study 2019 to measure disease burden and the NIH Research, Condition, and Disease Categories (RCDC) data to identify 60 disease categories aligned with available GBD data. NIH funding data was obtained from the RCDC system and the NIH Office of Budget. Using linear regression models, we observed that musculoskeletal diseases were among the most underfunded (i.e., negative residuals from the model) with respect to disease burden. Findings: Musculoskeletal diseases were underfunded, with neck pain being the most underfunded at only 0.83% of expected funding. Low back pain, osteoarthritis, and rheumatoid arthritis were also underfunded at 13.88%, 35.08%, and 66.26%, respectively. Musculoskeletal diseases were the leading cause of years lived with disability and the third leading cause in terms of prevalence and disability-adjusted life years. Despite the increasing burden of these diseases, the allocation of NIH funding to the National Institute of Arthritis and Musculoskeletal and Skin Diseases (NIAMS) has remained low compared to other institutes. Interpretation: Despite the increasing health burden and economic cost of $980 billion annually, the allocation of NIH funding to the NIAMS has remained low compared to other institutes. These findings suggest that the NIH may need to reassess its allocation of research funding to align with the current health challenges of our country. Furthermore, these clinically relevant observations highlight the need to increase research funding for musculoskeletal diseases and improve their prevention, diagnosis, and treatment. Funding: No funding.